Kajian Ritual Di Dalam Persembahan Tarian Bujang Ganong - Nooratika, Binti Pungot (Universiti Malaysia Sarawak (UNIMAS), 2018)
This research aims to study the Bujang Ganong dance performance and it elements ritual. The Setia Budi group from Kampung Parit Nipah, Batu Pahat, Johor has been chosen for collected more information towards Reog aesthetic that display the unique of Bujang Ganong dance performance. Through this study, the Bujang Ganong dance performance will be explained based on the genre characteristic similarity in 'The Fan' theory by Richard Schechner (1985). The importance of this research is to contribute a knowledge and awareness to community for better understand on the unique and aesthetic that found inside Bujang Ganong dance performance in Batu Pahat, Johor.